ENDOTHELIN-1, NITRIC OXIDE, AND RATIO OF ET1/NO IN ERECTILE DYSFUNCTION - Sinrang, Andi Wardihan (Indonesian Journal of Urology, 2011)
Objective: The aim of this study was to observe the level of Endothelin-1 (ET-1), Nitric oxide (NO), and the ratio of ET-1/NO in Erectile dysfunction (ED) and normal subjects. Material & method: This case-control study was carried out in Makassar with subjects recruited from outpatient clinic at Wahidin Sudirohusodo Hospital and divided into 2 groups (56 subjects DE and 34 subjects normal). ET-1 and NO plasma were measured by ELISA technique according to protocol. Results: The data showed that mean value of ET-1 in erectile dysfunction subjects was significantly higher (p < 0,05), while NO was significantly lower (p < 0,05) in DE groups compared to normal groups. The ratio of ET-1/NO was also significantly different between both groups. Conclusion: We concluded that level of plasma ET-1, plasma NO, and the ET-1/NO ratio are important factors involved in ED pathomechanism. Keywords: Erectile dysfunction, plasma endothelin-1, plasma nitric oxide, ratio ET-1/NO.